-31-11x=11-9x

Simple and best practice solution for -31-11x=11-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -31-11x=11-9x equation:


Simplifying
-31 + -11x = 11 + -9x

Solving
-31 + -11x = 11 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-31 + -11x + 9x = 11 + -9x + 9x

Combine like terms: -11x + 9x = -2x
-31 + -2x = 11 + -9x + 9x

Combine like terms: -9x + 9x = 0
-31 + -2x = 11 + 0
-31 + -2x = 11

Add '31' to each side of the equation.
-31 + 31 + -2x = 11 + 31

Combine like terms: -31 + 31 = 0
0 + -2x = 11 + 31
-2x = 11 + 31

Combine like terms: 11 + 31 = 42
-2x = 42

Divide each side by '-2'.
x = -21

Simplifying
x = -21

See similar equations:

| 8m+4=m | | 4r-7=8t+13 | | -74=-110+6x | | 14+6=2(5+7v)-4 | | 10n+5=5n+25 | | 5x-126=135-4x | | 9x-(x+22)=3x+3 | | 9x+10-5x=-12 | | 4+4b-3b=2+3b | | 3x+13=5x-3 | | 16-4=3(2-x) | | 7x+-7=12x+13 | | -3x+7y+14=0 | | 6x+68=2x-36 | | -4(-4X+6)=9 | | -117+12x=3x+90 | | 3(x+1)+x=x+8 | | 2(x+2)-6x=12 | | -2+3x+6-8x=-5 | | 2500=.5m | | x-57-57=-57 | | 5-4x+3=12 | | y=5(x-1) | | 14-13=5(1+4m)-2m | | -12+6x=12+8x | | 12p-7=-3p-8 | | 5x-4x-3=7 | | 16x+14=16+x | | 4(x+5)=4(2-x) | | X+6X-3(X-4)=4(X+2) | | 3x+10=5x-22 | | 3(x+1)+x=x-8 |

Equations solver categories